Pathophysiology of cerebral ischemia - Heiss, Wolf-Dieter (Henry Stewart Talks, 2008)
Cerebral ischemia, Stroke, Pathophysiology of ischemic brain damage, Penumbra, Reversible vs. irreversible brain damage, Imaging of development of ischemic damage, Imaging of development of ischemic damage in experimental models and patients with stroke